2012
DOI: 10.1016/j.vetpar.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Rotenoid content and in vitro acaricidal activity of Tephrosia vogelii leaf extract on the tick Rhipicephalus appendiculatus

Abstract: This study aimed to determine the rotenoid content of leaf extracts of the white (TVW) and purple (TVP) varieties of Tephrosia vogelii, both collected in North-Kivu Province, Democratic Republic of Congo and to evaluate their in vitro acaricidal efficacy on the tick Rhipicephalus appendiculatus. The high performance liquid chromatography analysis of rotenoid compounds from those extracts revealed that the contents of rotenone and deguelin were respectively higher in the leaves of TVW (0.044% and 1.13%) than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
2
14
1
4
Order By: Relevance
“…Our results indicate that T. vogelii is most widely used for pest control among other uses as shown in the survey results. Farmers' responses in this study, align with reports about the use of T. vogelii in controlling pests in vegetables and in stored products [15] and ectoparasite control in domestic animals [12,24,27]. The wider use of T. vogelii for small-scale farmers could be associated with previous projects that promoted integrated pest management using T. vogelii and research on soil improvement [28,29].…”
Section: Status Of Use Of Tephrosia Vogelii By Small Scale Farmerssupporting
confidence: 77%
See 1 more Smart Citation
“…Our results indicate that T. vogelii is most widely used for pest control among other uses as shown in the survey results. Farmers' responses in this study, align with reports about the use of T. vogelii in controlling pests in vegetables and in stored products [15] and ectoparasite control in domestic animals [12,24,27]. The wider use of T. vogelii for small-scale farmers could be associated with previous projects that promoted integrated pest management using T. vogelii and research on soil improvement [28,29].…”
Section: Status Of Use Of Tephrosia Vogelii By Small Scale Farmerssupporting
confidence: 77%
“…f. (Leguminosae) is a plant species reported to be used widely for its medicinal, insecticidal, and soil enrichment potential in tropical Africa [1][2][3][4][5][6]. Specifically, research on T. vogelii reported medicinal properties such as anti-cancer activity [7][8][9] and efficacy as an ectoparasite treatment for domestic animals including poultry [10][11][12][13][14]. A number of studies have sought to validate the reported use of T. vogelii as a botanical insecticide under laboratory and field conditions and have reported its effectiveness for crop protection and reduced impacts on beneficial ecosystem services [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of rotenoids, deguelin, rotenone, sarcolobine, tephrosin and α-toxicarol, in the leaves of T. vogelii, has been reported to be responsible for its pest control efficacy . Kalume et al (2012) reported that the rotenoid content of T. vogelii leaves was associated with its acaricidal activity against the cattle tick Rhipicephalus appendiculatus. Therefore, these compounds were mostly likely responsible for the observed acaricidal activity of T. vogelii leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…This is practiced in remote areas of Africa, commonly regarded as illegal fishing [61]. It is reported that leaves of T. vogelii contain high amounts of rotenone and deguelin [62] responsible for the toxicity to fish. Tephrosia vogelii has however a great potential in agriculture in the control of insect pests and in soil enrichment through nitrogen fixation [59].…”
Section: Tephrosia Vogeliimentioning
confidence: 99%